Meningkatkan Mutu ASN IHDN Denpasar dengan Pelayanan Publik Berbasis Tat Twam Asi - Ni Luh Gede Wariati (Jurnal Penjaminan Mutu, 2016)
The understanding and application of ethical values are essential in providing excellent service to the community. One kind of success of an institution is when it is able to provide excellent service to the community. Tat TvamAsi is one ofHindu philosophies that is loaded with ethical or moral values, it means that "he/she (him/her) is you." To provide excellent service, then it is highly needed innovations and efforts so that the goals can be realized as well. By applying the teachings of Tat TvamAsi, then ASN will realize that in fact we are all the same, then there will be no discrimination in providing services. IHDN is also one of the educational institutions that seek to improve quality in order to attract people to become members of the great family of this institute. To attract people and gain the trust of society, one of the efforts that can be done is to improve the quality of service in IHDN Denpasar. Tat Tvam Asi-based services could be a new innovation to improve the environmental quality of service in IHDN Denpasar.